Building Complexity and Achieving Selectivity through Catalysis – Case Studies from the Pharmaceutical Pipeline - Beaver, Matthew G.; Caille, Seb; Farrell, Robert P.; Rötheli, Andreas R.; Smith, Austin G.; Tedrow, Jason S.; Thiel, Oliver R. (Synlett, 2021)
The last decade of small-molecule process development has witnessed a trend of increasing molecular complexity for clinical candidates. The continued advance of novel catalytic methods and subsequent translation to efficient and scalable processes has enabled process chemists to overcome the challenges associated with increasing complexity. This Account highlights several examples from the process chemistry laboratories at Amgen.1 Introduction2 The Evolution of Molecular Complexity3 Catalysis as a Lever to Build Complexity4 Ru(II)-Catalyzed Dynamic Kinetic Resolution Enabling the Manufacture of AMG 2325 Application of Enzymatic Desymmetrization toward Scale-Up of the MCL-1 Inhibitor AMG 1766 Synthesis of Fucostatin 1: Catalytic Asymmetric Transfer Hydrogenation7 Manganese-Catalyzed Asymmetric Epoxidation To Prepare a Carfilzomib Intermediate8 Asymmetric Reduction Strategies: Novel Apelin Receptor Agonists and AMG 9869 Conclusions
Keywords: catalysis; process development; drug development; green chemistry; synthetic methods